Distal and proximal control of rhythmic gene transcription - Román-Figueroa, Abraham; Tenorio-Hernández, Luis; Furlan-Magaril, Mayra (Frontiers in Systems Biology, 2022)
The circadian clock synchronizes the temporal activity of physiological processes with geophysical time. At the molecular level circadian rhythms arise from negative feedback loops between activator and repressor transcription factors whose opposite and rhythmic activity at gene promoters sustains cyclic transcription. Additional epigenetic mechanisms driving rhythmic transcription involve dynamic remodeling of the proximal and distal chromatin environment of cyclic genes around the day. In this context, previous studies reported that thousands of enhancer elements display rhythmic activity throughout the 24 h and more recently, 3C-based technologies have shown that circadian genes establish static and rhythmic contacts with enhancers. However, the precise mechanisms by which the clock modulates gene topology are yet to be fully characterized and at the frontier of chronobiology. Here we review evidence of the proximal and long-distance epigenetic mechanisms controlling circadian transcription in health and disease.